Efektifitas Cognitive Behavior Therapy dalam Menurunkan Gejala Post Traumatic Stress Disorder Pasca Bencana: A Systematic Review - Supia Ningsih Juita Sari; Shrimarti Rukmini Devy; Hanik Endang Nihayati (FORIKES, 2021)
Background: The psychological impact that is often found in people affected by natural disasters is post-traumatic stress disorder. Traumatic events after an earthquake can cause psychological disorders, but psychological disorders can be minimized by changing cognitive patterns, behaviors that are based on a deep understanding of the problems experienced by patients. One of the most effective psychotherapy to overcome post-earthquake trauma is Cognitive behavioral therapy (CBT). Objective: To determine the effectiveness of cognitive behavior therapy in reducing post-disaster stress. Methods: This systematic review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The database used were Scopus, Proquest, Pubmed and, ScienceDirect, limited to the last 5 years of publication from 2016 to 2020, full-text article, in English. The keywords used in the article search were